The use of standardised tools to measure post-mastectomy quality of life among women in Africa: a scoping review - Alexis Harerimana; Gugu Mchunu (BMC Women's Health)
Abstract Background Breast cancer survivorship is increasingly prevalent, yet quality of life (QoL) outcomes post-mastectomy remain a critical concern in Africa. Women post-mastectomy encounter significant physical, psychological, social, and sexual health challenges that are inadequately addressed in clinical settings. Using standardised tools to measure QoL post-mastectomy of women is imperative. Thus, this scoping review aims to map evidence on the use of standardised tools to measure post-mastectomy quality of life among women in Africa. Methods This scoping review followed the Levac et al. framework. A systematic search—between 2015 and 2025 across Africa—yielded 473 records: 345 from five databases—CINAHL (n = 22), Emcare (n = 55), Medline (n = 65), Scopus (n = 78), and Web of Science (n = 125)—and 128 from other sources. Ultimately, 34 studies met the inclusion criteria for data extraction and thematic analysis. The review followed PRISMA-ScR guidelines. Results The 34 studies reviewed involved 5466 participants. Mean ages ranged from 38 to 57 years. QoL post-mastectomy was evaluated using standardised tools such as the EORTC QLQ-C30/BR23, WHOQOL-BREF, BREAST-Q, and FACT-B. Several studies translated and validated QoL assessment tools into local languages, notably Arabic and Yoruba, enhancing contextual relevance. Mastectomy negatively affected overall QoL, body image, psychological wellbeing, sexual functioning, and social relationships. Educational and psychosocial interventions enhanced QoL, particularly those integrating self-compassion training, physical rehabilitation, and group counselling. Conclusion QoL post-mastectomy among women in Africa is significantly compromised; however, targeted psychosocial and rehabilitation interventions show promise in improving survivorship outcomes. Future research should emphasise culturally sensitive, multidisciplinary programs and adopt longitudinal designs to assess sustained effects on QoL. Implications for cancer survivors This scoping review emphasises the need for comprehensive post-mastectomy care that includes physical, psychological, sexual, social and financial aspects. Culturally sensitive and accessible interventions are essential for improving the quality of life and long-term outcomes for women in Africa.